El acompañamiento emocional de los padres de familia en el periodo de adaptación de los niños del nivel inicial 2, de la Unidad Educativa Combatientes de Tapi, de la ciudad de Riobamba, provincia Chimborazo. - Moyota Garcia, Mishell Elizabeth (2023)
The main objective of this research is to determine the influence of the parent's emotional support in the adaptation period of the children of the Initial Level 2 of the Combatientes de Tapi Educational Unit in Riobamba city. Considering that the support and affection, both physical and verbal, from the parents is relevant during this process, the theoretical framework supports the approached topic; therefore, information is found on emotional support, how to provide emotional support during childhood, the family, affective bond, the adaptation period, primary considerations, the role of those involved, importance and consequences. Methodologically, the research comprises a qualitative approach, with a non-experimental design, of bibliographic and transversal type, by the level it is estimated as descriptive and field, the study sample is integrated by 20 children and 20 parents of the initial level 2 parallel 'A,' the techniques used were the observation and survey each one with its respective instrument; the observation card with eight items directed to the infants and the questionnaire with ten items destined to the parents. It was identified that some children make present difficulties when adapting to the school environment since there was evidence of crying, sadness, anger, and lack of integration; concerning the surveys, most parents consider that emotional support is essential in this period. It is concluded that the emotional support from parents influences how the child adapts to the institution. Therefore, children need their parents to provide security and unconditional support for the stage to become satisfactory.